NAD(P) transhydrogenase isoform distribution provides insight into apicomplexan evolution - Tremp, Annie Z.; Saeed, Sadia; Dessens, Johannes T. (Frontiers in Ecology and Evolution, 2023)
Membrane-located NAD(P) transhydrogenase (NTH) catalyses reversible hydride ion transfer between NAD(H) and NADP(H), simultaneously translocating a proton across the membrane. The enzyme is structurally conserved across prokaryotes and eukaryotes. In heterotrophic bacteria NTH proteins reside in the cytoplasmic membrane, whereas in animals they localise in the mitochondrial inner membrane. Eukaryotic NTH proteins exists in two distinct configurations (isoforms) and have nonmitochondrial functions in unicellular eukaryotes like Plasmodium, the causative agent of malaria. In this study, we carried out a systematic analysis of nth genes across eukaryotic life to determine its prevalence and distribution of isoforms. The results reveal that NTH is found across all major lineages, but that some organisms, notably plants, lack nth genes altogether. Isoform distribution and phylogenetic analysis reveals different nth gene loss scenarios in apicomplexan lineages, which sheds new light on the evolution of the Piroplasmida and Eimeriidae.